A Mathematical Model for Wind Velocity Field Reconstruction and Visualization Taking into Account the Topography Influence - Guzel Khayretdinova; Christian Gout (Journal of Imaging, 2024)
In this paper, we propose a global modelling for vector field approximation from a given finite set of vectors (corresponding to the wind velocity field or marine currents). In the modelling, we propose using the minimization on a Hilbert space of an energy functional that includes a fidelity criterion to the data and a smoothing term. We discretize the continuous problem using a finite elements method. We then propose taking into account the topographic effects on the wind velocity field, and visualization using a free library is also proposed, which constitutes an added value compared to other vector field approximation models.